Effectiveness of intermittent training in hypoxia combined with live high/ train low - Robertson, E. Y.; Saunders, P. U.; Pyne, D. B.; Gore, C. J.; Anson, J. M. (European Journal of Applied Physiology, 2010)
Elite athletes often undertake altitude training to improve sea-level athletic performance, yet the optimal methodology has not been established. A combined approach of live high/train low plus train high (LH/TL+TH) may provide an additional training stimulus to enhance performance gains. Seventeen male and female middle-distance runners with maximal aerobic power VO2max of 65.5 ± 7.3 mL kg-1 min-1 (mean ± SD) trained on a treadmill in normobaric hypoxia for 3 weeks (2,200 m, 4 week-1). During this period, the train high (TH) group (n = 9) resided near sea-level (~600 m) while the LH/TL+TH group (n = 8) stayed in normobaric hypoxia (3,000 m) for 14 hours day-1. Changes in 3-km time trial performance and physiological measures including VO2maxrunning economy and haemoglobin mass (Hbmass) were assessed. The LH/TL+TH group substantially improved VO2max(4.8%; ±2.8%, mean; ±90% CL), Hbmass (3.6%; ±2.4%) and 3-km time trial performance (-1.1%; ±1.0%) immediately post-altitude. There was no substantial improvement in time trial performance 2 weeks later. The TH group substantially improved VO2max(2.2%; ±1.8%), but had only trivial changes in Hbmass and 3-km time-trial performance. Compared with TH, combined LH/TL+TH substantially improved VO2max(2.6%; ±3.2%), Hbmass (4.3%; ±3.2%), and time trial performance (-0.9%; ±1.4%) immediately post-altitude. LH/TL+TH elicited greater enhancements in physiological capacities compared with TH, however, the transfer of benefits to time-trial performance was more variable.